(untitled) (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Type 5 Diabetes Mellitus (T5DM), also known as Malnutrition-Related Diabetes Mellitus (MRDM), is a distinct and underrecognized form of diabetes associated with chronic undernutrition. Although considered rare, it is not uncommon in developing countries like Bangladesh, where malnutrition remains a widespread issue. Diabetes mellitus, a multifactorial endocrine disorder, is associated with both chronic undernutrition and obesity. Malnutrition often involves deficiencies in macro- and micronutrients in prenatal or postnatal life, unhealthy lifestyle behaviors, and low socioeconomic status. Numerous clinical studies have highlighted the connection between malnutrition and diabetes. Diagnostic challenges, overlapping symptoms, and an unclear causal relationship between malnutrition and diabetes hinder its classification and management. Current global diabetes frameworks inadequately address T5DM, contributing to misdiagnosis and delayed treatment. Malnutrition predominantly results in persistent insulin deficiency, glucose intolerance, and insulin resistance, thereby increasing the risk of developing diabetes. Further research is essential to refine the diagnostic criteria, elucidate the underlying pathophysiology, and assess the clinical and public health benefits of formally recognizing T5DM as a distinct subtype of diabetes mellitus. J Assoc Clin Endocrinol Diabetol Bangladesh, July 2025;4(2): 72-79